Cash for tropical peat: land use change and forestry projects for climate change mitigation - MacDicken, K.G. (Agency for the Assessment and Application of Technology (BPPT) and Indonesian Peat Association (IPA), 2002)
While tropical peat swamps can present very large stocks, the threat of greenhouse gas emissions to the atmosphere is much lower. Given the current agreement for activities to be conducted through the Clean Development Mechanism (afforestation and reforestation only), it seems there is little opportunity for peat swamp project because they are unlikely to effectivelly compete with projects on terra firma. There is still a chance that forest conservation could be included as a project alternative in the future commitment periods. It is important that scientists working on tropical peat swamps seek to influence policy makers to include forest conservation in the Kyoto Protocol if peat swamps are to be conserved through climate change mitigation mechanisms.